Screening of Jiangshui-originated lactic acid bacteria with high hypoglycemic properties and study on functional properties of Jerusalem artichoke Jiangshui - Gui, Yan-Wen; Jin, Qing-kai; Yao, Hui; Sheteiwy, Mohamed S.; Mohammed, Afrah E.; Alotaibi, Modhi O.; Chang, Si-Jing; Meng, Xian-Gang (Frontiers in Microbiology, 2025)
The current study was designed to evaluate and characterize lactic acid bacteria (LAB) with high hypoglycemic properties isolated from Northwest Jiangshui. The strain was identified as Lactobacillus paracasei and designated as LAB 815. Saccharomyces cerevisiae strain [SC 8(3)] was selected from the laboratory-preserved yeasts as the most suitable aroma-producing yeast for co-fermenting Jerusalem artichoke (JA) Jiangshui with LAB 815. In vitro assays of hypoglycemic and uric acid-lowering abilities, together with antioxidant activity against free radicals (DPPH, -OH and superoxide anion), revealed that LAB strain exerted inhibitory effects on α-amylase, α-glucosidase, glucose dialysis delay index, xanthine oxidase, DPPH radicals, hydroxyl radicals and superoxide anion radicals, with inhibition rates of 61.79, 53.26, 55.67, 83.46, 96.64, 88.76, and 79.06%, respectively. Gastrointestinal fluid simulation experiments demonstrated that cooperation between LAB 815 and SC 8(3) markedly mitigated the adverse effects of the highly acidic gastrointestinal environment. Antimicrobial assays showed that JA Jiangshui significantly inhibited the growth of several spoilage bacteria. These results indicate that co-fermentation of JA tubers with LAB 815 and SC 8(3) to produce JA Jiangshui confers significant health benefits and represents a promising approach for managing diabetes and hyperuricemia.